2003
DOI: 10.1039/b109928k
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio and DFT modelling of complex materials: towards the understanding of electronic and magnetic properties of polyoxometalates

Abstract: In this review we summarise the quantum chemistry studies carried out by several groups over the last ten years on polyoxometalates, or polyoxoanions. This is an immense family of compounds made up of transition metal ions in their highest oxidation state and oxo ligands. The continuous progress of computers in general, and quantum chemistry software in particular, has enabled a number of topics in polyoxometalate chemistry to be studied from the electronic structure of the most representative polyoxometalate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
191
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(200 citation statements)
references
References 41 publications
8
191
0
1
Order By: Relevance
“…The composition of the precipitates was determined as [PW 12 O 40 3¹ ]:2 = 2:3. The average DLS diameter of (2) 3 [PW 12 O 40 ] 2 redispersed in water was 99 « 4 nm ( Figure S4, SI), which showed a zeta potential of ¹33 mV, similar to that observed for (1) (Figure 2c), which are in remarkable contrast to the regular parallelepiped nanocrystals formed by (1) 3 [PW 12 O 40 ] 2 . It is to be noted that the introduction of ether linkages in counter ions promotes the formation of uniform polyhedron nanocrystals.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…The composition of the precipitates was determined as [PW 12 O 40 3¹ ]:2 = 2:3. The average DLS diameter of (2) 3 [PW 12 O 40 ] 2 redispersed in water was 99 « 4 nm ( Figure S4, SI), which showed a zeta potential of ¹33 mV, similar to that observed for (1) (Figure 2c), which are in remarkable contrast to the regular parallelepiped nanocrystals formed by (1) 3 [PW 12 O 40 ] 2 . It is to be noted that the introduction of ether linkages in counter ions promotes the formation of uniform polyhedron nanocrystals.…”
mentioning
confidence: 45%
“…Polyoxometalates (POMs) are transition metal oxide clusters with negative charges, which exert a wide range of catalytic, 1 electronic, 2 magnetic, 3 and photochemical 4 properties. These unique physical and chemical properties render POMs key components for various applications, including nanodevices and medical science.…”
mentioning
confidence: 99%
“…The bridging oxygen atoms of the POMs are more nucleophilic than the terminal ones [22]. Theoretical calculations indicated that the µ 2 bridging atoms within the [W 5 O 18 ] groups can be more easily protonated than those shared between them [23].…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Becke [43] and Perdew [44] gradient corrections were used for the exchange and correlation energy, respectively. The basis functions for describing the valence electrons of the atoms are Slater-type orbitals of triple-zeta plus polarization TZP quality; these have been used to investigate the properties of POMs [26,28,30,45]. The internal or core electrons (1s for oxygen, 1s for carbon, 1s-3d for niobium, 1s-4d for tungsten) were frozen and described by single Slater functions.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Our group has investigated the electronic properties, stabilities, and nonlinear optical properties of POMs using DFT methods [18][19][20][21][22]. DFT has proved to be an important tool for understanding and rationalizing the properties of polyanions [23][24][25][26][27][28][29][30]. In this work, our main objective is to investigate the effects of methoxy groups on the electronic properties of POMs.…”
mentioning
confidence: 99%